2016
DOI: 10.13057/biodiv/d170229
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, anatomy, and mycorrhizal fungi colonization in roots of epiphytic orchids of Sempu Island, East Java, Indonesia

Abstract: Roots of orchids have important role for survival, adaptation, water and nutrient absorption, and as a place of symbiosis with mycorrhizal fungi. The present study aimed to investigate the morphology, anatomy, and mycorrhizal status in roots of orchids of Sempu Island, Indonesia (Ascochilus emarginatus, Taeniophyllum biocellatum, and Thrixspermum subulatum), in relation to their adaptation to their habitat of coastal forests of Sempu Island. These orchids have different morphological characters; Ascochilus ema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
(57 reference statements)
0
12
0
1
Order By: Relevance
“…Leaves of T. biocellatum are absent but they have green roots that contain chloroplasts. The presence of chloroplasts confirmed in the anatomical roots characters of T. biocellatum (Nurfadilah et al, 2016). There must be conserve of the T. biocellatum in its natural habitat while maintaining the presence of trees serving as the host for the epiphytic orchid.…”
Section: Epiphytic Orchids Hoya and Dischidia In Bawean Island Naturmentioning
confidence: 68%
“…Leaves of T. biocellatum are absent but they have green roots that contain chloroplasts. The presence of chloroplasts confirmed in the anatomical roots characters of T. biocellatum (Nurfadilah et al, 2016). There must be conserve of the T. biocellatum in its natural habitat while maintaining the presence of trees serving as the host for the epiphytic orchid.…”
Section: Epiphytic Orchids Hoya and Dischidia In Bawean Island Naturmentioning
confidence: 68%
“…Although D. subulatum did not exhibit to posses spiral thickenings in the mesophyll, it had fibre bundles that have the same function as spiral thickenings (discussed above). In the previous study, spiral thickenings were also found in the cortical roots of A. emarginatus (Nurfadilah et al 2016).…”
Section: Spiral Thickeningmentioning
confidence: 67%
“…Previous studies on orchids anatomy in Indonesia have been conducted including anatomical characters of roots of orchids of Sempu Island (Nurfadilah et al 2016), leaf anatomy of nine species of Bulbophyllum (Orchidaceae) (Betty 2011), comparative leaf and root anatomy of two species of Dendrobium (Metusala et al 2017). The present study of orchid leaf anatomy provides additional data to support species identification and to increase understanding of orchid biology and ecology, concerning structural adaptation of orchids in coastal habitats in Sempu Island.…”
Section: Introductionmentioning
confidence: 92%
“…Root presented a 2-3 layered velamen, showing helical cell wall thickenings. Such a restricted number of velamen layers is characteristic of species belonging to relatively humid habitats [71]. Velamen avoids the loss of moisture from roots, speeds up water absorption, and provides protection against mechanical stresses and ultraviolet radiations [72,73].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, helical thickenings in the velamen cells have the function to improve the stability and efficiency of this tissue for water absorption by the root and its retention in dry conditions in epiphytic orchids [74]. Passage cells constitute a channel for the selective transit of nutrients and water, and for the entrance of mychorrhizal fungi [71,75,76]. Tilosomes, branched lignified wall ingrowths on the internal periclinal wall of the endovelamen cells, are typically positioned near passage cells [77,78].…”
Section: Discussionmentioning
confidence: 99%